Risk Factors and Survival Analysis of COVID-19 Among Health Care Workers in West Jakarta Hospital - Virmandiani Virmandiani; Asri C Adisasmita; Febby Elvanesa Sandra Dewi (Acta Medica Indonesiana)
Background: The first two cases of Coronavirus Disease 2019 (COVID-19) were identified in Indonesia on March 2nd, 2020. Health Care workers (HCWs) are at risk of contracting COVID-19 infection. This study analyzed the risk factors, compared the prevalence rate of COVID-19 between HCWs and non-HCWs, and investigated survival analysis describing the time risk of COVID-19. Methods: This prospective cohort study retrieved data from the Hospital Surveillance Team (one of the largest hospitals in West Jakarta) which were analyzed using descriptive, bivariate analysis, Survival Analysis through the Kaplan-Meier method, and multivariate Cox analysis. Results: Observations were conducted on 1,080 employees from March 2021 to March 2022. There were 192 employees (17.78%) of 40±11 years tested positive for COVID-18, of which 126 cases (16.84%) were HCWs of ≤ 40 years of age, with females dominating. There was no difference between HCW and Non-HCW; ARR=1.08; [95% IK, 0.83-1.43]; p=0.591. Workers on shift work (> 38 hours in a week) were likely to be affected by COVID-19 with RR=1.37; [95% IK, 1.06-1.78]; p=0.018. Kaplan–Meier method and the log-rank test showed the difference between Shift and Non-shift groups HR=1.43; [95% IK 1.06-1.94]; p=0.019. Asthma or Chronic Obstructive Pulmonary Disease appeared as the independent factor of COVID-19 infection with RR=1.82; [95% IK, 1.10-3.02]; p=0.031. Conclusion: The probability of contracting COVID-19 was found equal to HCW and Non-HCW. Employees who are on shifts have a greater probability of contracting COVID-19. Survival analysis showed a statistically different Hazard Ratio between shifts with Non-shift workers.